Bimbingan Karakter Islami Melalui Pesantren Program Di Daarut Tauhiid Bandung - Ulyani, Farida (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Guidance Of Islamic Character Through An Islamic Boarding School Program In Daarut Tauhiid Bandung. To carry out the great mission of Islam to develop Islamic character requires a cultural space that is unified in structure and culture. This effort is carried out, among others, through pesantren. This paper examines the process of guiding Islamic character through the Pesantren Program at Daarut Tauhiid Bandung. With a case study approach, data on observations, interviews and documentation were analyzed by means of discovery analysis. An important finding of this research is that the mentoring process requires an intensive program planning process with clear and measurable objectives. This is like being held at the Daarut Tauhiid Islamic Boarding School in Bandung. Of the various pesantren programs that have been held such as: the Santri Training for Morals and Entrepreneurship, Santri Ready to Use Program, Daurah Ma'rifatullah Program, Student Islamic Boarding School Program and the Dauroh Qolbiyah Intensive These Programs were a form of structured symbolic interaction involving power mechanisms between students, Kyai, Ustadz and also community environment, including the congregation of the mosque. So to build or guide Islamic character requires cultural awareness and at the same time cultural intelligence so that local wisdom-based guidance becomes interesting and relevant to be developed in the context of Islamic character guidance as held at Daarut Tauhiid as a best practice that should be adopted for other institutions.Keywords: Guidance, Islamic Character, Islamic Boarding School